2001
DOI: 10.1521/soco.19.4.418.20758
|View full text |Cite
|
Sign up to set email alerts
|

Individual Versus Group Interest Violation: Surprise as a Determinant of Argument Scrutiny and Persuasion

Abstract: Previous studies based on an attributional analysis of persuasion have suggested that a source who takes an unexpected position is perceived as more trustworthy and accurate than one who argues for an expected position. As a result, message processing is decreased when expectancies are violated compared to when they are confirmed. The current research suggests that these findings are limited to cases in which the unexpected position violates individual self-interest.When a source's unexpected position violates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…Research indicates that people are more likely to scrutinize messages from sources seen as less trustworthy [3537]. Though we did not identify medical institutions as the source of BD information, coupling it with information about a new medical device may have made medical institutions more salient, thus leading to greater scrutiny of BD information among AA women, and indirectly linking BD information to intentions via its effects on attitudes.…”
Section: Discussionmentioning
confidence: 81%
“…Research indicates that people are more likely to scrutinize messages from sources seen as less trustworthy [3537]. Though we did not identify medical institutions as the source of BD information, coupling it with information about a new medical device may have made medical institutions more salient, thus leading to greater scrutiny of BD information among AA women, and indirectly linking BD information to intentions via its effects on attitudes.…”
Section: Discussionmentioning
confidence: 81%
“…Unfortunately, restrictions in the report of initial agreement with the message compared with the control groups for different levels of ability and motivation prevented us from examining this important question. However, a broader exploration of attitude change processes could do so.Cognitive conflict and persuasion-Past research has shown that cognitive conflict of the kind present in the sleeper effect can enhance issue-relevant thinking (e.g., Albarracín, 2002;Baker & Petty, 1994;Berlyne, 1965;Chaiken & Maheswaran, 1994;Eagly, Chaiken, & Wood, 1981;Jonas, Diehl, & Bromer, 1997;Maheswaran & Chaiken, 1991;Petty, Fleming, Priester, & Feinstein, 2001). Thus, receiving a discounting cue first and then receiving cogent arguments may lead communication recipients to engage in further elaboration of those arguments.…”
mentioning
confidence: 99%
“…1 There has recently been a noticeable shift in theoretical developments that recognizes that neither majorities nor minorities are associated exclusively with a particular process and that each source can be associated with systematic or non-systematic processing, and can lead to different outcomes, under different conditions (Brandstätter et al, 1991;Martin & Hewstone, 2003b). For example, several researchers have found that, contrary to conversion theory, a majority can lead to message processing, when the topic is high in outcome relevance (Crano & Chen, 1998;Trost, Maass, & Kenrick, 1992), when the source argues for a negative personal outcome (Baker & Petty, 1994;Martin & Hewstone, 2003b; see also Petty, Fleming, Priester, & Feinstein, 2001), when an experimental manipulation focuses attention on the source (Bohner, Frank &, Erb, 1998;De Dreu & De Vries, 1993) or on the content of the message , when the source position is invalidated (Brandstätter et al, 1991), or when attention is increased via ingestion of caffeine (Martin & Martin, 2006). This pattern of findings has led to a greater emphasis on contingency approaches, which specify that the processes involved in majority and minority influence are contingent upon some additional factors (e.g., conflict elaboration theory, Mugny et al, 1995;Pérez & Mugny, 1996; context/comparison model, Crano & Alvaro, 1998; and the source-position congruency model, Baker & Petty, 1994).…”
mentioning
confidence: 99%